Optical filters and resonant cavities based on di-ureasil organic-inorganic hybrids - Vicente, C. M. S.
Sol-gel derived poly(oxyethylene)/siloxane organic-inorganic di-ureasil hybrids containing different amounts (20-60% mol) of methacrylic acid (McOH) modified zirconium oxo-clusters (Zr-OMc) were processed as thin films and transparent and shape controlled monoliths. Laser direct writing was used to create channel waveguides, Bragg gratings, Fabry-Perot cavities and optical filters. The resulting Fabry-Perot optical cavity displays a free spectral range of 16.55 GHz and a fringe intensity contrast of 5.35 dB. Optical rejection values between 6.7 and 10.4 dB were obtained by varying the amount of the Zr-OMc oxo-clusters.